Value creation and co-creation in advisory board : case Kasvun Roihu Ltd and Nordea Growth program - Tehomaa, Reetta (2017)
The goal of this research is to create deeper understanding, what kind of value Nordea Growth program created for its interest groups, and find the main factors behind the success of advisory boards. The goal of Nordea Growth program was to improve 20 small and medium sized companies readiness for financing and growth by building them advisory boards for a year. The program was organized by Kasvun Roihu Ltd and Nordea Plc. Research was executed as qualitative singular case study and its empirical part was executed by interviewing 10 persons. Interviewees represented all the interest groups of the program and interview method was individual narrative interview. As an analysis method in research was used three stage content analysis model. According to this research Nordea Growth program created value for all of its interest groups, but the level of perceived value varied strongly between different interest groups and persons. According to research the value perceived by award-winning companies can be divided into four themes, which are challenging and encouraging, new ideas, new contacts, and financing. Growth Board members perceived value can be divided into three themes, which are change in normal work, learning, and joy of helping others. Nordea’s perceived value can be divided into four themes, which are new perspectives for Nordea’s employees work, possible new customerships and development of existing ones, new relations between Nordea and external advisors, and positive influence on the brand. According to research there are seven main factors behind the success of Growth Board. These main factors are the leading role of the company, concrete and realistic targets, open atmosphere, company’s readiness to receive challenging, company’s functional ability, suitable Growth Board members, sufficient meeting preparations, and time and attendance. Based on the research’ results some development ideas for implementation, selling and marketing of this service concept was made and also new process map for this service concept was build.